1997
DOI: 10.1104/pp.115.2.511
|View full text |Cite
|
Sign up to set email alerts
|

Separation of Photolabile-Phytochrome and Photostable-Phytochrome Actions on Growth and Microtubule Orientation in Maize Coleoptiles (A Physiological Approach)

Abstract: For separating the physiological actions of photolabile (phy-I) and photostable phytochromes, we compared the effects of red (R) and far-red (FR) light on elongation growth and microtubule reorientation in segments of maize (Zea mays L.) coleoptiles raised either in darkness (phy-l present) or preirradiated with R (phy-l eliminated). In 4.5-d-old dark-grown seedlings R first promoted growth and induced a transverse microtubule orientation. In continuous R the phytochrome action responsible for these responses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…For example, wounding induces a transient, systemic Ca 2+ -dependent increase in membrane-associated PLD as well as an increase in PA (Ryu and Wang 1996, Lee et al 1997, Wang et al 2000, and also leads to realignment of microtubules (Hush et al 1990). Phytochrome activation increases PLD-dependent PA production, probably through a G-protein-mediated pathway (Park et al 1996), and phytochrome also affects the orientation of microtubules (Fischer and Schopfer 1997). Similarly, bacterial infection increases PLD levels and promotes its localisation to the plasma membrane (Young et al 1996), while fungal pathogens cause microtubules to focus at the infection site (Kobayashi et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“…For example, wounding induces a transient, systemic Ca 2+ -dependent increase in membrane-associated PLD as well as an increase in PA (Ryu and Wang 1996, Lee et al 1997, Wang et al 2000, and also leads to realignment of microtubules (Hush et al 1990). Phytochrome activation increases PLD-dependent PA production, probably through a G-protein-mediated pathway (Park et al 1996), and phytochrome also affects the orientation of microtubules (Fischer and Schopfer 1997). Similarly, bacterial infection increases PLD levels and promotes its localisation to the plasma membrane (Young et al 1996), while fungal pathogens cause microtubules to focus at the infection site (Kobayashi et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“…However, another plausible explanation may refer to the physiological differences between hypocotyls and roots, especially in relation to the interplay between strigolactone signaling and light perception. As mentioned previously, light-induced microtubule reorientations in aboveground tissues have been shown to correlate with phytochrome ( Zandomeni and Schopfer, 1993 ; Fischer and Schopfer, 1997 ) and phototropin ( Lindeboom et al, 2013 ) signaling. The roots are also not indifferent to light, since dim light gradients may form at shallow depths of the soil and probably express specialized photoreceptors responsive to low illumination rates especially at the blue wavelength range ( Galen et al, 2007 ; Wan et al, 2019 ).…”
Section: Discussionmentioning
confidence: 66%
“…Owing to the previous connection of strigolactones with phytochrome and cryptochrome light perception pathways, the differential responses of cortical microtubule to strigolactone content alterations under light or dark growth conditions is expected. Earlier studies have already demonstrated the interdependence between phytochromes and light-induced microtubule reorientation ( Fischer and Schopfer, 1997 ), while more recently, the reorientation of cortical microtubule under blue light stimulation was attributed to activation of KATANIN-mediated microtubule severing via the activation of the PHOT1 and PHOT2 phototropin photoreceptors ( Lindeboom et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Realignment of plant's CMT arrays is induced by various environmental and developmental factors including light (Cyr 1994, Le et al 2005, Lian et al 2017, Ma et al 2018. Although there are some reports about the involvement of phytochrome in the reorganization of CMT arrays (Zandomeni and Schopfer 1993, Fischer and Schopfer 1997, Ma et al 2018, these studies were conducted on the aerial parts of the plants. Our results provide a novel finding which shows involvement of phytochrome in the regulation of CMT arrays in roots.…”
Section: Involvement Of Phytochrome In Cmt Randomizationmentioning
confidence: 99%